Quality Improvement of Overhaul Maintenance Service using Servqual and Quality Function Deployment Method Case Study in PT. Pembangkitan Jawa Bali (PJB) UPHT Gresik - Adi Suryadarma; Moses Laksono Singgih (IPTEK Journal of Proceedings Series, 2020)
Electricity is the right of every person guaranteed in the 1945 Constitution, it must be realized in the form of providing electricity supply for the community. Electricity generators in Gresik are one of the power suppliers for industries and communities through the distribution managed by one of the electricity distributor in Indonesia. As time goes by, the plant needs to do a planned maintenance called overhaul. This research aims to improve the quality of overhaul maintenance service to one of the generators that exist in Gresik. The other goal is to know what service factors that affect the level of customer satisfaction in accordance with customer expectations based on service priority variables. Measurement of service quality of overhaul maintenance is done by combining ServQual method and Quality Function Deployment (QFD) method.